A Compact Wideband Circularly Polarized Microstrip Slot Antenna with Parasitic Elements. (28th September 2021) - Xia, Chenhui; Diao, Shuo; Yin, Wenting; Huang, Zhifang; Wang, Lei; Lei, Dengyun
Abstract : A compact wideband circularly polarized (CP) microstrip slot antenna (MSA) with parasitic elements is designed in this letter. The CP MSA comprises a square-loop sequential-phase (SP) feeding configuration, four rotated rectangular patches, and four L -shaped slots embedded in the ground plane. The square-loop SP feeding structure comprises a square loop and an arc-shaped strip, which could provide a 270° phase difference. Four rotated rectangular patches are placed at the edge of the square-loop feeding configuration using a capacitively tightly coupled feeding method to stimulate the CP resonant mode. After selecting these elements and tuning proper dimensions, the broad operating bandwidths of 4.38–5.25 GHz (18%) for | S 11 | <–10 dB and 4.65–5.31 GHz (13.2%) for AR <3 dB could be realized. Hence, the designed CP MSA has a potential application value in wireless communication.